SPEECH PERCEPTION ON STUDENTS ACTIVITY AT STKIP AL MAKSUM LANGKAT (A CASE STUDY OF PSYCHOLINGUISTICS) - maitri rahmadhani (CV MEDAN TEKNO SOLUSI, 2023)
This paper investigates the speech perception on students activity especially for the third-semester students at STKIP Al Maksum Langkat. It focuses to find Speech perception on students activity (especially in third semester students) at STKIP Al Maksum and to explain the reason why it runs that way. The research design used is case study, especially the observal case study in which the instrument of the data is the speech perception test. It was found that: a) a phenomenon called as Coarticulation that also deals with Voice Onset Time is occured in experiment-1, b)some words cannot be perceived well because they are categorized as rare word, c) The hearer did not made mistake in hearing some words becuse of Personal Values or Interests, d) some mistakes in reading words and sentences because the room had not enough light that causing the reading activities hard be carried out, e) some words are correct (in reading) because the students used Visual Recognition Threshold, f) The performance will be improved if the lights is turned back on and no noisy sound that interrupt the speech perception process.